Deviation of paradigmatic mutations found in Shprintzen-Goldberg syndrome - Nandy, Arnab; Das, Sankar K.; Roy, Sumit; Das, Shreyasi (International Journal of Contemporary Pediatrics, 2019)
Shprintzen-Goldberg (S-G) Syndrome known as rare congenital connective tissue disorder where craniosynostosis and marfanoid habitus found to be the usual presentation. Craniofacial dysmorphism with multi-organ involvement documented to be amongst prominent features of this syndrome. Case characteristics is five-month-old male infant with craniosynostosis, and motor developmental delay was evaluated for congenital connective tissue disorder. Dysmorphic craniofacial features like dolichocephaly, triangular forehead, ocular hypertelorism, micrognathia and retrognathia were noticed besides congenital umbilical hernia, empty scrotal sac, clinodactyly with long slender fingers, hyper-mobile joints, hypotonia. Subsequent investigations revealed normal male karyotype (46, XY) while genetic analysis depicted missense mutations in six different genes. Conventionally, mutation in SKI gene reported for its’ associated with S-G syndrome where dysregulation of TGF-β signaling was discussed as the primary reason. In the present case discussed here, it was found to have polygenic mutational association where few novel genetic mutations were seen.